Invertebrados acuáticos asociados a raíces de macrófitas Pistia stratiotes y Eichhornia crassipes en el río Itaya, Comunidad Moena Caño. Iquitos, Perú - Salas Marquillo, Genny Esther (2025)
Various groups of aquatic invertebrates inhabit the root systems of macrophytes; however, the representative groups are unknown. The objective was to understand the composition of aquatic invertebrates associated with the roots of Pistia stratiotes and Eichhornia crassipes. Samples were collected six times every two weeks from January to March 2024 in the Itaya River, Moena Caño community, Iquitos, Peru. Three sampling zones were established (zone 1: entrance to the channel, zone 2: middle section, and zone 3: end of the channel). Two sampling points were set up per zone: point 1: Pistia stratiotes, and point 2: Eichhornia crassipes. Five aquatic macrophytes were collected, making a total of 90 individuals per macrophyte. For microinvertebrate collection, macrophyte roots were manually squeezed, while for macroinvertebrates, the plant was placed in a white tray for root searching. Richness consisted of 9 phyla, 16 classes, 23 orders, and 37 families, with Arthopoda being the most diverse phylum and the orders with the largest families being Coleoptera and Hemiptera. Abundance was 19,559 individuals, with Arcellidae and Lecanidae being the most abundant; zone 3 was the most abundant, higher than the other zones. We concluded that there were no significant differences (p > 0.05) in the number of aquatic invertebrate families between the different zones, for both Pistia stratiotes and Eichhornia crassipes.